Analisis Kesiapan Masyarakat Terhadap Implementasi Program Smart City Kota Kupang - Donita Geraldine Gella; Christantius Dwiatmadja (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The city of Kupang as one of the cities in the province of East Nusa Tenggara (NTT) takes part in the smart city program by building a regional smart city. The main goal of Smart City in Kupang city is to improve people's welfare, including development, infrastructure, service management and the public environment. This research was conducted using a survey technique to the people of Kupang city with the research method being quantitative and using purposive sampling method. The results of the measurement of Kupang City Community Readiness for the Smart City program, it was concluded that the Kupang City community was READY based on the measurement results through the indicators of Awareness, Governance, Business resources, Human resources, Technology resources, Adoption.